The Effect of Learning Media on Learning Outcomes of Volleyball Bottom Passing on Deaf Students: Pengaruh Media Pembelajaran terhadap Keberanian Passing Bawah Bola Voli pada Siswa Tunarungu - hendya junanda; Sandi Dwi Triono (STKIP Paasundan Press, 2022)
The purpose of this study was to examine the effect of using instructional media on the courage to learn volleyball underarm pass in Sekolah Luar biasa Citeureuo Cimahi. The method used is experimental research. The present study involved 12 students consisting 6 students in the experimental group and 6 students in the control group. To measure students’ was used while learning output is measured by a volleyball underarm pass test. Data analysis is conducted by paired test or t-test. There is an influence of the use of parachute as media on the courage in volleyball underarm pass. These findings showed that the use of parachute as media in volleyball match revealed to be effective in increasing deaf students’ courage.